2017
DOI: 10.1111/ap.12269
|View full text |Cite
|
Sign up to set email alerts
|

The Supervision Evaluation and Supervisory Competence Scale: Psychometric Validation

Abstract: Objectives:The last two decades has witnessed a strong endorsement of competency-based models for both practitioner training and professional supervision. The valid and reliable measurement of supervisee and supervisory competence is an essential step towards progress, yet currently there are few instruments that can claim to measure the range of supervisor competencies. The current study establishes the Supervision Evaluation and Supervisory Competence (SE-SC) scale as a new, psychometrically sound instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 41 publications
0
17
0
2
Order By: Relevance
“…based on their style (Heinonen, 2014 ). Therapists tend to act in a variety of ways, as different studies using cluster analysis as a methodology have shown (Gonsalvez, Hamid, Savage, & Livni, 2017 ; Kaur, Grover, & Desai, 2015 ; Montaño-Fidalgo, Ruiz, Calero-Elvira, & Froján-Parga, 2015 ). This study went beyond the PST construct, since a comprehensive assessment of therapist’s personality was conducted, a variable noted by previous studies as being closely attached to the professional’s work style (Boerebach et al, 2014 ; Chapman, Talbot, Tatman, & Britton, 2009 ; Peter, Böbel, Hagl, Richter, & Kazén, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…based on their style (Heinonen, 2014 ). Therapists tend to act in a variety of ways, as different studies using cluster analysis as a methodology have shown (Gonsalvez, Hamid, Savage, & Livni, 2017 ; Kaur, Grover, & Desai, 2015 ; Montaño-Fidalgo, Ruiz, Calero-Elvira, & Froján-Parga, 2015 ). This study went beyond the PST construct, since a comprehensive assessment of therapist’s personality was conducted, a variable noted by previous studies as being closely attached to the professional’s work style (Boerebach et al, 2014 ; Chapman, Talbot, Tatman, & Britton, 2009 ; Peter, Böbel, Hagl, Richter, & Kazén, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A lot of research is being done on the training of professional counsellors in countries such as Australia, the UK, and Canada (Carroll 2009;Carroll 1994;Chang 2013;Gonsalvez and Mcleod 2008;Gonsalvez et al 2002;Johnson and Stewart 2000;Milne 2007;Milne et al 2008;Milne and Dunkerley 2010). The supervision research in these countries has focused on defining supervision, refining theories and models of supervision, and exploring the effectiveness of supervision, supervisor training, competence, and best practices in supervision (Gonsalvez 2014;Gonsalvez and Calvert 2014;Gonsalvez and Freestone 2007;Gonsalvez et al 2017;Gonsalvez and Mcleod 2008;Gonsalvez and Milne 2010;Milne and Watkins 2014;Milne et al 2011). However, in countries in Asia, Africa, and the Caribbeanwhere counsellor supervision is still in the early stageslittle literature is available on the supervision of interns (Amer 2013;Fang et al 2014;Stupart et al 2010;Watkins 2014).…”
Section: Status Of Counsellor Supervision Globallymentioning
confidence: 99%
“…Since then we are aware of four new instruments that assess competence directly, though none represents progress in rating CBT supervision. Specifically, the ‘supervisory competence scale’ (Gonsalvez et al ., 2017) relies on supervisees’ ratings, which the authors acknowledged to be a biased and simplistic measure. A similar problem exists with the self-ratings made by supervisors receiving training in supervision (Newman-Taylor et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…', p. 87). More recently, Gonsalvez et al (2017) reached a similar conclusion, arguing for greater psychometric rigour in the development of instruments, but some progress has been noted (Watkins and Milne, 2014), including a 'core outcome battery' to address the lack of cumulative progress (Wheeler and Barkham, 2014). However, the resulting 'toolkit' of six instruments, selected to support routine data collection in practitioner-led research, are all self-report questionnaires.…”
mentioning
confidence: 98%